Enhancing Emergency Response through Artificial Intelligence in Emergency Medical Services Dispatching; a Letter to Editor - Emami, Payam; Javanmardi, Karim (Archives of Academic Emergency Medicine, 2023)
The emergency medical dispatcher (EMD) serves as a crucial link between individuals in need of emergency medical assistance and the emergency medical services (EMS) resource delivery system. Through their expertise and training, EMDs are able to accurately assess emergency situations, provide appropriate guidance over the phone, and dispatch the necessary EMS personnel to the scene. With adequate training, program management, supervision, and medical guidance, the EMD can accurately assess the caller’s needs, choose an appropriate response approach, furnish relevant information to responders, and offer suitable assistance and guidance to patients through the caller. By diligently adhering to a written and medically approved EMD protocol, informed decisions regarding EMS responses can be made in a reliable, replicable, and fair manner (1, 2).